Management of healthcare organizations : an introduction - Olden, Peter C.; Erwin, Cathleen O. (Association of University Programs in Health Administration, 2023)
"This introductory textbook teaches students timeless fundamental principles of healthcare management. Combined with contemporary methods and current information, theory and practice, students will gain an understanding of healthcare management organizations and know how to use new tools, concepts, models, and methods when it is their turn to lead"--